2014
DOI: 10.1371/journal.pone.0109441
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin Assembly Protein CALM Plays a Critical Role in KIT Signaling by Regulating Its Cellular Transport from Early to Late Endosomes in Hematopoietic Cells

Abstract: CALM is implicated in the formation of clathrin-coated vesicles, which mediate endocytosis and intracellular trafficking of growth factor receptors and nutrients. We previously found that CALM-deficient mice suffer from severe anemia due to the impaired clathrin-mediated endocytosis of transferrin receptor in immature erythroblast. However, CALM has been supposed to regulate the growth and survival of hematopoietic stem/progenitor cells. So, in this study, we focused on the function of CALM in these cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…1a). In this condition, in accord with our previous report 24 , FL-induced phosphorylation of FLT3 WT, SCF-induced phosphorylation of KIT WT, and phosphorylation of their downstream molecules (STAT5, ERK, and Akt) were not impaired, while phosphorylation of Akt was slightly augmented and prolonged in Ba/F3-FLT3 WT and Ba/F3-KIT WT by CALM KD ( Supplementary Fig. 1b).…”
Section: Calm Is Required For Oncogenic Signals In Mt-rtk Aml Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…1a). In this condition, in accord with our previous report 24 , FL-induced phosphorylation of FLT3 WT, SCF-induced phosphorylation of KIT WT, and phosphorylation of their downstream molecules (STAT5, ERK, and Akt) were not impaired, while phosphorylation of Akt was slightly augmented and prolonged in Ba/F3-FLT3 WT and Ba/F3-KIT WT by CALM KD ( Supplementary Fig. 1b).…”
Section: Calm Is Required For Oncogenic Signals In Mt-rtk Aml Cellssupporting
confidence: 92%
“…These findings are largely consistent with the phenotypes of fit1 mice harboring a nonsense point mutation in the PICALM gene 22,23 . Furthermore, we showed that CALM is essential for CCV formation and plays an important role in the intracellular trafficking of KIT from early to late endosomes in hematopoietic cells 24 . In this study, we also found that KIT-mediated cellular growth was partially impaired in CALM −/− HSC/HPCs.…”
mentioning
confidence: 90%
“…that ALMS1 may be involved in lipid raft-dependent NKCC2 endocytosis. However, we also pulled down phosphatidylinositol binding clathrin assembly protein (PICALM) ( Figure 1E), which mediates clathrin-dependent endocytosis and targeting of clathrin-coated vesicles to early and late endosomes (47). Together, our data suggest that ALMS1 may be a common scaffold that recruits proteins involved in determining lipid raft-and/or clathrin-dependent endocytosis.…”
Section: Figure 5 Alms1-ko Rats Have Higher Nkcc2-mediated Nacl Absomentioning
confidence: 82%
“…Some recent studies found that Picalm is related to apoptosis and that apoptosis was increased in Picalm -deficient erythroblasts 26 . SCF-induced KIT trafficking was severely impaired in CALM -deficient MEFs leading to the excessive activation of Akt 27 . Knockdown of CALM stimulated autophagosome formation but overexpression decreased autophagy, which protects cells against proapoptotic insults by reducing caspase activation 28 .…”
Section: Discussionmentioning
confidence: 99%